PEMBUBARAN PERSEROAN TERBATAS BERDASARKAN PUTUSAN HAKIM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA PUTUSAN NOMOR: 253PK/PDT/2012 - DESSY SAIDA SRY HADINI SIMBOLON (PREMISE LAW JURNAL, 2017)
PT. Ve Wong Budi Indonesia which runs its business in the production of food seasoning. The company was liquidated due to disputes among the stakeholders over the company liquidation, equal share entitlement or almost equal share position. These disputes have caused loss to the company. It shows obscurity in the indicator of the District Court about the liquidation of the limited company with the reason that the company cannot proceed, in accordance with Article 146, paragraph (1), letter c of UUPT (Law on Limited Company). Therefore, the problems that rise are what forms the basis of the District Court so that it can liquidate a limited company, how the panel of judges decides the company liquidation, how the panel of judges considers the liquidation of PT. Ve Wong Budi Indonesia, and what its legal consequences are to the stakeholders. Keywords: Liquidation, Limited Company, Judge’s Ruling